EMC for product designers - Williams, Tim, ....- (Amsterdam : Newnes, 2010)
Widely regarded as the standard text on EMC, Tim Williams' book provides all the key information needed to meet the requirements of the latest EMC Directive. Most importantly, it shows how to incorporate EMC principles into the product design process, avoiding cost and performance penalties, meeting the needs of specific standards and resulting in a better overall product. As well as covering the very latest legal requirements, the fourth edition has been thoroughly updated in line with the latest best practice in EMC compliance and product design. Coverage has been considerably expanded to include the R&TTE and Automotive EMC Directives, as well the military aerospace standards of DEF STAN 59-41 and DO160E. A new chapter on systems EMC is included, while short case studies demonstrate how EMC product design is put into practice.
Keywords: Elektromagnetisme